Pengaruh Motivasi Konsumen dalam Pembelian Produk Donat Lylo di Kabupaten Pinrang - Israh Israh; Nurhapsa Nurhapsa; A. Erna Sriwahyuningsih (Universitas Muslim Maros, 2023)
The buying decision process by consumers is influenced by the motivation or drive within them to fulfill their needs and desires, namely by recognizing needs, seeking information on a product, evaluating alternatives, then deciding to buy until the behavior that occurs post-purchase, so that consumers can achieve satisfaction from their needs and desires. the wish fulfilled. The purpose of this study was to determine the effect of consumer motivation in purchasing Lylo Donut products in Pinrang Regency in terms of product quality, service quality and promotion. This study uses a data collection method using a questionnaire with a sample of 90 respondents using purposive sampling method. The analysis technique uses multiple linear regression analysis which is processed with SPSS version 21. From the results of the study it is known that product quality, service quality and promotion have a positive influence on consumer motivation. The result of the calculation of the coefficient of determination is 0.423. This shows that product quality, service quality and promotion are able to explain consumer motivation by 42.3%. while the remaining 57.7% is explained by other variables that are not observed. Based on the results of data analysis, it can be concluded that there is a positive influence of product quality, service quality and promotion on consumer motivation in purchasing Lylo Donuts, Pinrang Regency.